Towards an effective privacy impact and risk assessment methodology: risk assessment - Alshammari, M; Simpson, AC (Springer, Cham, 2018)
It is increasingly recognised that Privacy Impact Assessments (PIAs) play a crucial role in providing privacy protection for data subjects and in supporting risk management for organisations. However, existing PIA processes are typically not accompanied with proper guidelines and/or methodologies that sufficiently support privacy risk assessments and illustrate precisely how the core part of the PIA—a risk assessment—can be conducted. We present an approach for assessing potential privacy risks built upon a privacy risk model that considers legal, organisational, societal and technical aspects. This approach has the potential to underpin a systematic and traceable privacy risk-assessment methodology that can complement PIA processes.